2022
DOI: 10.1177/21582440221138069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Teaching Metacognitive Reading Strategies on Reading Comprehension of Engineering Students

Abstract: This experimental research investigates the impact of teaching metacognitive reading strategies on the reading comprehension of engineering students in the English for Science and Technology(EST) context. This research is the first empirical study of its kind in Libyan English as a Foreign Language (EFL/EST) context. The study utilizes the Survey of Reading Strategies (SORS) and a reading comprehension achievement test extracted from ‘Oxford English for Computing’ by Boechner and Brown (instruction manual). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…These results suggest that problem-solving strategies were effective in promoting reading test scores, regardless of question formats. These findings aid previous research, clarifying that students' metacognitive knowledge positively impacts their reading test scores [10,11,[14][15][16][17][18][19][20][21]. However, these positive effects were largely attributed to problem-solving strategies [11,23,29] and were not restricted by question formats.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results suggest that problem-solving strategies were effective in promoting reading test scores, regardless of question formats. These findings aid previous research, clarifying that students' metacognitive knowledge positively impacts their reading test scores [10,11,[14][15][16][17][18][19][20][21]. However, these positive effects were largely attributed to problem-solving strategies [11,23,29] and were not restricted by question formats.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, Seedanont and Pookcharoen (2019) [19], Mohseni et al (2020) [17], and Khellab et al (2022) [16] investigated the instruction of metacognitive strategies in English as a foreign language (EFL) classes and reported similar findings. Seedanont and Pookcharoen (2019) [19] and Khellab et al (2022) [16] examined students' English reading test scores before and after weeks of instruction on metacognitive strategy use, while Mohseni et al (2020) [17] compared the reading performance of three groups: one receiving training on metacognitive strategy use, another receiving training on reading awareness, and a control group. All three studies concluded that instruction in metacognitive strategies significantly increased students' reading test scores.…”
Section: Metacognitive Knowledge and L2 Readingmentioning
confidence: 81%
See 1 more Smart Citation
“…Metacognitive strategies involve planning, monitoring, thinking, and evaluating a learning task during or after it occurs (Khellab et al, 2022;Richards & Schmidt, 2002). In the items loaded around this factor, learners think about learning experiences to do them better for the second time (item 1), reflect on the thinking process to improve learning procedures (item 3), reflect on learning beliefs and values to understand better to enhance their learning (items 4, 5), analyze learning experiences to get a new understanding (item 2), think over learning experiences to evaluate the outcome of learning (item 8).…”
Section: Metacognitive Process: Items Loading On Factor 3 Tap Into Me...mentioning
confidence: 99%
“…Research has underscored the role of metacognitive awareness in enhancing reading comprehension across various educational contexts (Algraini, 2022;Anderson, 2002;Carrell et al, 1989;Khellab et al, 2022;Mokhtari & Reichard, 2002). In light of this, proficiency in MRS becomes particularly crucial for EFL learners situated in culturally diverse settings, such as Iran.…”
Section: Introductionmentioning
confidence: 99%